1996
DOI: 10.1126/science.274.5291.1379
|View full text |Cite
|
Sign up to set email alerts
|

Liver Failure and Defective Hepatocyte Regeneration in Interleukin-6-Deficient Mice

Abstract: Liver regeneration stimulated by a loss of liver mass leads to hepatocyte and nonparenchymal cell proliferation and rapid restoration of liver parenchyma. Mice with targeted disruption of the interleukin-6 (IL-6) gene had impaired liver regeneration characterized by liver necrosis and failure. There was a blunted DNA synthetic response in hepatocytes of these mice but not in nonparenchymal liver cells. Furthermore, there were discrete G1 phase (prereplicative stage in the cell cycle) abnormalities including ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

64
1,254
6
21

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,415 publications
(1,345 citation statements)
references
References 39 publications
64
1,254
6
21
Order By: Relevance
“…Several publications have documented that both oncogenic Ras and oncogenic Raf can stimulate proliferation and suppress differentiation in SV40 virus immortalized hepatocytes [9,10]. Since both oncogenic Ras and oncogenic Raf will cause potent activation of the MAP kinase cascade, these data would initially appear to be in conflict with our results.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Several publications have documented that both oncogenic Ras and oncogenic Raf can stimulate proliferation and suppress differentiation in SV40 virus immortalized hepatocytes [9,10]. Since both oncogenic Ras and oncogenic Raf will cause potent activation of the MAP kinase cascade, these data would initially appear to be in conflict with our results.…”
Section: Discussioncontrasting
confidence: 76%
“…Partial hepatectomy or acute dissociation by collagenase treatment and primary culture of hepatocytes triggers their entry into the cell cycle [1][2][3][4][5][6][7][8][9][10]. Maximal DNA synthesis in i o occurs 12-36 h post partial hepatectomy and within 5-7 days the liver has regained its original mass [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Mere A20 heterozygous knockdown transformed PH from a well-tolerated procedure to one with more than 40% lethality, uncovering an otherwise unsuspected phenotype in HET mice. Remarkably, lethality in HET mice topped that of IL-6 KO, 30 TNF-receptor-1 KO 31 and conditional hepatocyte-specific STAT3 KO, 32 qualifying A20 among the most potent key physiologic regulators of LR.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in this pathway, for example, STAT-3 deficiency in macrophages and neutrophils, lead to the constitutive activation of these cells and result in progression to chronic inflammation (39) similar to the phenotype of Plg -/-mice in the current study. In studies of liver wound healing, large areas of necrosis can be found in the liver of both IL-6 -/-and Plg -/-mice (40,41). In the current study, we found that levels of IL-6 and IL-10 expression are higher in infected joints of Plg ϩ/ϩ mice than in those of Plg -/-mice, and supplementation with human plasminogen increased the expression of IL-6 in the infected knee joints.…”
Section: Discussionmentioning
confidence: 99%